(untitled) (Bangladesh Heart Journal, 2024)
Background: Acute myocardial infarction is one of the leading causes of death across the world. Determination of severity is important in patients with acute myocardial infraction for the therapeutic decision making. Neutrophil to Lymphocyte Ratio (NLR) has been proposed as a new prognostic marker in patients with acute MI. Several international studies have found to compare the relation between NLR and severity of coronary artery disease. In these studies, they demonstrated that the NLR is higher in severe CAD. In our country no such study has been done yet to predict the severity of coronary artery disease by estimating NLR in acute MI patients. Moreover, NLR is cheap, easily available, non-invasive and routinely done procedure. Objectives: This study was conducted to find out the association of NLR to severity of CAD in acute MI patients. Methods: This observational cross sectional analytical study was carried out in the Department of Cardiology, Dhaka Medical College Hospital, SSMC and Mitford Hospital and NICVD, Dhaka from March 2021 to February, 2022. Patients with acute MI (STEMI and NSTEMI) were approached for this study according to inclusion and exclusion criteria. They were divided into two groups according to NLR: Group A NLR >2.5 and Group B NLR ≤2.5. Coronary angiogram was done during index hospitalization. The severity of coronary artery disease was assessed by Vessel score and Gensini score. According to Gensini score was non severe (≤50) severe (>50). Results: Among 70 patients in our study 30 (42.8%) were in the high NLR group (Group A) and 40 (57.14%) were in low NLR group (Group B). In group A mean NLR was 5.15 ± 2.21 and in group B mean NLR was 1.65 ± 0.35, this difference was statistically significant. Severe coronary artery disease in terms of vessel score and Gensini score was significantly higher in group A than group B (p value 0.001). We found strong positive correlation between NLR and Gensini score (r= 0.7, p= 0.001), and moderate positive correlation between NLR nad vessel score (r= 0.5, p= 0.001). With the increase of NLR, vessel score and Gensini score increases demonstrating more severe CAD. Simple logistic regression analysis of variables of interest revealed that hypertension (p=0.003), diabetes mellitus (p=0.008), dyslipidaemia (p=0.007), WBC count(p=0.034), Neutrophil count (p=0.000), Lymphocyte count (p=0.000), NLR (p=0.000), LVEF (p=0.001) were independent predictor of severe coronary artery disease with odds ratio (OR) being 5.32, 3.88, 4.42, 1.00, 1.20, 0.834, 2.28, 0.805 respectively. In multivariate logistic regression analysis, after adjustment of confounding, hypertension (p=0.028, OR=5.87) and NLR (P=0.004, OR=1.81) remain independent predictor of severe CAD. In ROC curve analysis, the AUC of NLR for predicting severity of CAD is 0.8 with p value < 0.001, 95% CI (0.78-0.96) and with 75% sensitivity and 86.5% specificity. So, from this study, it is evident that NLR is directly associated with coronary artery disease severity. Conclusion: Increased NLR was associated with angiographically severe coronary artery disease in acute Myocardial Infarction patients, and this association is independent of conventional cardiovascular risk factors. Bangladesh Heart Journal 2024; 39(1): 1-9